Endothermic composition and heat-absorbing board
Patent Information
- Application Number
- JP2024148127
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2024-05-02
- Filing Date
- 2024-08-30
- Publication Date
- 2025-03-14
AI Technical Summary
【0008】 本発明の吸熱性組成物は、防火性に優れる。
Smart Images

Figure 2025036357000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a novel heat absorbing composition and a heat absorbing board. [Background technology]
[0002] In general, fireproof materials are provided in building materials, vehicle materials, etc., for example, to suppress the inflow and outflow of heat from the outside and to increase the heat resistance of the materials. By providing such fireproof materials, the internal environment can be protected for a certain period of time in a high-heat environment or in the event of a fire. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 9-302804 [Patent Document 2] JP 2019-6852 A Summary of the Invention [Problem to be solved by the invention]
[0004] As such fireproof materials, for example, Patent Document 1 describes gypsum board and the like, and Patent Document 2 describes a fireproof material using a flame retardant and fiber-reinforced resin and the like. However, such materials may not provide sufficient fire protection.
[0005] The present invention has been made in view of the above problems, and an object of the present invention is to provide a material having excellent fire retardancy. [Means for solving the problem]
[0006] As a result of intensive research aimed at solving the above problems, the present inventors have found that an endothermic composition containing a binder including an unsaturated polyester and an unsaturated monomer, and a specific amount of sodium tetraborate hydrate has excellent fire retardancy, leading to the completion of the present invention.
[0007] That is, the present invention has the following features. 1. A composition comprising a binder and sodium tetraborate hydrate; The binder comprises an unsaturated polyester and an unsaturated monomer. An endothermic composition comprising: 2. The endothermic composition according to 1, characterized in that the sodium tetraborate hydrate is contained in an amount of 30 parts by mass or more and 300 parts by mass or less per 100 parts by mass of the binder. 3. The endothermic composition according to 1, wherein the sodium tetraborate hydrate comprises sodium tetraborate decahydrate. 4. The endothermic composition according to 1, further comprising a layered clay mineral. 5. The endothermic composition according to 4, wherein the mixing ratio (weight ratio) of the binder to the layered clay mineral is 100:0.1 or more and 100:8 or less. 6. The mixing ratio (mass ratio) of the sodium tetraborate hydrate to the layered clay mineral is 100:0.1 or more and 100:10. 4. The endothermic composition according to claim 4. 7. The endothermic composition according to 4., wherein the layered clay mineral includes bentonite. 8. An endothermic board formed from the endothermic composition according to any one of 1. to 7. Effect of the Invention
[0008] The endothermic composition of the present invention has excellent fire retardancy. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, an embodiment of the present invention will be described.
[0010] The endothermic composition of the present invention is characterized by containing a binder and sodium tetraborate hydrate.
[0011] (Binding Agent) The binder is characterized by containing an unsaturated polyester and an unsaturated monomer.
[0012] (Unsaturated polyester) The unsaturated polyester may be, for example, one produced by an esterification reaction between a polyhydric alcohol and a polybasic acid.
[0013] Examples of the polyhydric alcohol include alkylene glycols such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, and neopentyl glycol, trimethylolethane, trimethylolpropane, glycerin, pentaerythritol, 1,6-hexanediol, ester glycol, 1,4-cyclohexanedimethanol, and 1,3-butanediol, and these can be used alone or in combination of two or more.
[0014] Examples of the polybasic acid include unsaturated polybasic acids such as maleic acid, maleic anhydride, fumaric acid, itaconic acid, itaconic anhydride, and citraconic acid. Phthalic acid (orthophthalic acid), isophthalic acid, terephthalic acid, phthalic anhydride, tetrahydrophthalic acid, tetrahydrophthalic anhydride, hexahydrophthalic acid, hexahydrophthalic anhydride, cyclohexanedicarboxylic acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, azelaic acid, sebacic acid, trimellitic acid, and pyromellitic acid can also be used in combination, and one or more of these can be used.
[0015] (Unsaturated Monomer) Examples of the unsaturated monomer include (meth)acrylic acid ester monomers such as methyl (meth)acrylate, and aromatic monomers such as styrene, methylstyrene, and divinylbenzene, and one or more of these can be used.
[0016] In particular, it is preferable to use, as the unsaturated polyester, one produced by an esterification reaction between a polyhydric alcohol selected from ethylene glycol and propylene glycol and a polybasic acid selected from maleic acid, maleic anhydride, fumaric acid, and isophthalic acid, and, as the unsaturated monomer, a (meth)acrylic acid ester monomer and / or an aromatic monomer.
[0017] In the present invention, the mixing ratio of the unsaturated polyester and the unsaturated monomer is preferably 10 parts by mass or more and 200 parts by mass or less, more preferably 20 parts by mass or more and 180 parts by mass or less, relative to 100 parts by mass of the unsaturated polyester. By mixing the unsaturated polyester and the unsaturated monomer in such a range and, if necessary, adding an initiator, etc., it is possible to obtain an unsaturated polyester resin having excellent fire resistance and strength, and a heat absorbing board using the unsaturated polyester resin.
[0018] The binder may contain other binders in addition to the unsaturated polyester and unsaturated monomer as long as the effects of the present invention are not impaired. Other binders include, for example, polyether resin, polyester resin, unsaturated polyester resin, vinyl acetate resin, alkyd resin, epoxy resin, acrylic resin, acrylic silicone resin, urethane resin, phenol resin, melamine resin, polycarbonate resin, fluororesin, acrylic-vinyl acetate resin, acrylic-urethane resin, acrylic-epoxy resin, acrylic-silicone resin, silicone modified acrylic resin, ethylene-vinyl acetate resin, cement, and gypsum.
[0019] (Sodium tetraborate hydrate) The sodium tetraborate hydrate is a component that imparts endothermic properties. As the sodium tetraborate hydrate, from the viewpoint of endothermic properties, sodium tetraborate pentahydrate and sodium tetraborate decahydrate are more preferable, and among them, sodium tetraborate decahydrate is particularly preferable from the viewpoint of excellent endothermic properties, since a large amount of hydration water is liberated from the hydrate and the temperature at which it is liberated is relatively low (about 60° C.).
[0020] The sodium tetraborate pentahydrate is a substance that liberates water of hydration at approximately 100 to 150° C. The sodium tetraborate decahydrate is a substance that liberates water of hydration at approximately 60° C. In particular, the sodium tetraborate hydrate preferably contains 50% by mass or more (even more preferably 70% by mass or more, and even more preferably 100% by mass) of sodium tetraborate decahydrate.
[0021] The particle size of the sodium tetraborate is preferably 1 μm to 5 mm, more preferably 3 μm to 1 mm, even more preferably 5 μm to 500 μm, and most preferably 10 μm to 300 μm. By being in such a range, storage stability can be improved, warping and distortion can be suppressed, and formability can be improved.
[0022] The content of the sodium tetraborate hydrate is preferably 30% by mass or more and 75% by mass or less (further, 40% by mass or more and 70% by mass or less, furthermore, 45% by mass or more and 65% by mass or less) of the entire endothermic composition. Within such a range, an endothermic board having sufficient heat absorption and strength can be obtained.
[0023] The endothermic composition of the present invention can be obtained by mixing other additives in addition to the above-mentioned components. Examples of the other additives include layered clay minerals, fillers, flame retardants, curing agents, dispersants, surfactants, curing accelerators, foaming agents, foam stabilizers, viscosity adjusters, initiators, metal hydrates, colorants, dyes, film-forming assistants, leveling agents, wetting agents, plasticizers, antifreeze agents, pH adjusters, preservatives, antifungal agents, anti-algae agents, antibacterial agents, adsorbents, fibers, carbonizing agents, and solvents.
[0024] The layered clay mineral is a component that imparts storage stability to the endothermic composition during storage, inhibits warping and distortion during board production, and also contributes to formability. Examples of the layered clay minerals include smectite, bentonite, vermiculite, kaolinite, allophane, mica, talc, halloysite, and sepiolite. One or more of these may be used, and those containing bentonite are particularly preferred. In addition, it is preferable to use an organically treated layered clay mineral as the layered clay mineral, and examples of the organic treatment include ion exchange (intercalation) of cations present between the layers of the layered clay mineral with long-chain alkyl ammonium ions, etc.
[0025] Specific examples of organically treated bentonite include Esben, Esben C, Esben E, Esben W, Esben P, Esben WX, Esben NX, Esben NZ, Esben N-400, Organite, Organite-D, and Organite-T (product names) manufactured by Hojun Co., Ltd.; TIXOGEL MP, TIXOGEL VP, TIXOGEL VP, TIXOGEL MP, TIXOGEL EZ 100, MP 100, TIXOGEL UN, TIXOGEL DS, TIXOGEL VP-A, TIXOGEL VZ, TIXOGEL PE, TIXOGEL MP 250, and TIXOGEL MPZ (product names) manufactured by Süd-Chemie Catalysts; and BENTONE 34, 38, 52, 500, 1000, 128, 27, SD-1, and SD-3 (product names) manufactured by Elementis Japan.
[0026] The mixing ratio (solids weight ratio) of the binder and the layered clay mineral is preferably 100:0.1 or more and 100:8 or less (preferably 100:0.3 or more and 100:5 or less, more preferably 100:0.5 or more and 100:3 or less). By using such a mixing ratio, the sodium tetraborate hydrate and the layered clay mineral are uniformly mixed in the binder, which provides excellent storage stability, suppresses warping and distortion during board production, and provides a heat absorbing board with excellent formability.
[0027] In the present invention, the mixing ratio (mass ratio of solid content) of the sodium tetraborate hydrate and the layered clay mineral is preferably 100:0.1 or more and 100:10 or less (preferably 100:0.5 or more and 100:5 or less). By being in such a range, the sodium tetraborate hydrate and the layered clay mineral are uniformly mixed in the binder, which gives excellent storage stability and suppresses warping and distortion during board production, making it possible to obtain a heat absorbing board with excellent formability.
[0028] Examples of the filler include heavy calcium carbonate, kaolin, diatomaceous earth, white carbon, clay, talc, barite powder, precipitated barium sulfate, barium carbonate, silica sand, vermiculite, ceramic beads, glass beads, silica gel, perlite, expanded vermiculite, pumice, vermiculite, crushed ALC, hollow ceramic beads, hollow glass beads, shirasu balloons, charcoal, bamboo charcoal, seed shell charcoal, smoked seed shell charcoal, styrene resin foam, ethylene vinyl acetate resin foam, polyvinyl chloride resin foam, and the like. One or more of these may be used.
[0029] The amount of the filler to be mixed may be 0.1 to 100 parts by mass (or more preferably 0.5 to 50 parts by mass) relative to 100 parts by mass of the binder (solid content). Within this range, excellent strength can be exhibited while ensuring light weight.
[0030] In particular, in the present invention, the filler has a bulk density of 0.01 g / cm 3 More than 1g / cm 3 A lightweight filler having a mass of less than 10 ... Furthermore, in the present invention, one or more non-combustible lightweight fillers selected from perlite, expanded vermiculite, pumice, vermiculite, crushed ALC, ceramic hollow beads, hollow glass beads, charcoal, bamboo charcoal, seed shell charcoal, and smoked seed shell charcoal can be used.
[0031] The amount of the lightweight filler to be mixed may be 100 parts by mass or less (even 50 parts by mass or less) relative to 100 parts by mass of the binder (solid content). The amount of the lightweight filler in this range is advantageous in terms of lightness and strength. In addition, if the lightweight filler is a non-flammable lightweight filler, it is also advantageous in terms of fire resistance.
[0032] The bulk density of the filler is a value measured by supplying the filler to a cylindrical container and applying up and down vibration (tapping vibration) to the filler in the container until the bulk change of the filler in the container ends.
[0033] The average particle size of the filler is not particularly limited, but may be from 50 μm to 1000 μm. The average particle size of the filler can be measured by a laser diffraction particle size distribution measuring device.
[0034] Examples of the flame retardant include phosphorus-based flame retardants, halogen-based flame retardants, boron-based flame retardants, metal hydroxide-based flame retardants, nitrogen-based flame retardants, and silicon-based flame retardants, and one or more of these can be used.
[0035] Examples of the phosphorus-based flame retardant include phosphate ester compounds, phosphate compounds, polyphosphate compounds, phosphite compounds, phosphonate compounds, phosphonite compounds, phosphinate compounds, phosphinate compounds, red phosphorus, phosphorus trichloride, and phosphorus pentachloride.
[0036] Specific examples of the phosphoric acid ester compound include trimethyl phosphate, triethyl phosphate, tributyl phosphate, trioctyl phosphate, triphenyl phosphate, trisnonylphenyl phosphate, tributoxyethyl phosphate, tricresyl phosphate, cresyl phenyl phosphate, cresyl diphenyl phosphate, octyl diphenyl phosphate, trixylenyl phosphate, diisopropyl phenyl phosphate, tris(2-ethylhexyl)phosphate, resorcinol bisdiphenyl phosphate, bisphenol A bis(diphenyl phosphate), resorcinol bisdixylenyl phosphate, tris(chloroethyl)phosphate, tris(chloropropyl)phosphate, tris(dichloropropyl)phosphate, bis(2, 3-dibromopropyl)-2,3-dichloropropyl phosphate, tris(2,3-dibromopropyl)phosphate, bis(chloropropyl)monoctyl phosphate, hydroquinonyl diphenyl phosphate, phenyl nonyl phenyl hydroquinonyl phosphate, phenyl dinonyl phenyl phosphate, diphenyl-4-hydroxy-2,3,5,6-tetrabromobenzyl phosphonate, dimethyl-4-hydroxy-3,5-dibromobenzyl phosphonate, diphenyl-4-hydroxy-3,5-dibromobenzyl phosphonate, trialkyl polyphosphate, resorcinol polyphenyl phosphate, bisphenol A polycresyl phosphate, resorcinol poly(di-2,6-xylyl)phosphate, hydroquinone poly(2,6-xylyl)phosphate, and the like.
[0037] Examples of the phosphate compound include aluminum phosphate, sodium phosphate, potassium phosphate, calcium phosphate, zinc phosphate, ammonium phosphate, aluminum phosphite, sodium phosphite, potassium phosphite, calcium phosphite, zinc phosphite, ammonium phosphite, aluminum hypophosphite, sodium hypophosphite, potassium hypophosphite, calcium hypophosphite, zinc hypophosphite, ammonium hypophosphite, aluminum metaphosphate, sodium metaphosphate, potassium metaphosphate, calcium metaphosphate, and zinc metaphosphate.
[0038] Examples of the polyphosphate compound include ammonium polyphosphate, ammonium amide polyphosphate, melamine polyphosphate, piperazine polyphosphate, melem polyphosphate, melam polyphosphate, melon polyphosphate, and aluminum polyphosphate.
[0039] Examples of the phosphonate compound include methylphosphonic acid, dimethyl methylphosphonate, diethyl methylphosphonate, ethylphosphonic acid, propylphosphonic acid, butylphosphonic acid, 2-methylpropylphosphonic acid, t-butylphosphonic acid, 2,3-dimethyl-butylphosphonic acid, octylphosphonic acid, phenylphosphonic acid, and dioctyl phenylphosphonate.
[0040] Examples of the phosphinic acid salt compound include dimethylphosphinic acid, methylethylphosphinic acid, methylpropylphosphinic acid, diethylphosphinic acid, dioctylphosphinic acid, phenylphosphinic acid, diethylphenylphosphinic acid, diphenylphosphinic acid, and bis(4-methoxyphenyl)phosphinic acid.
[0041] The halogen-based flame retardants include, for example, those containing fluorine, chlorine, bromine, iodine, and antimony, and examples thereof include halogen oxides, halogenated phosphazenes, halogenated alkanes, halogenated indanes, halogenated phosphates, and halogenated polystyrenes.
[0042] Examples of the boron-based flame retardants include boron oxide, boric acid, lithium borate, sodium borate (excluding sodium tetraborate), potassium borate, cesium borate, magnesium borate, calcium borate, barium borate, zirconium borate, zinc borate, aluminum borate, and ammonium borate.
[0043] Examples of the metal hydroxide-based flame retardant include aluminum hydroxide, magnesium hydroxide, calcium hydroxide, iron hydroxide, nickel hydroxide, zirconium hydroxide, zinc hydroxide, titanium hydroxide, copper hydroxide, tin hydroxide, and vanadium hydroxide.
[0044] The amount of the flame retardant mixed is preferably 0.1 to 100 parts by mass (more preferably 0.3 to 80 parts by mass, even more preferably 0.5 to 50 parts by mass, and even more preferably 0.8 to 30 parts by mass) relative to 100 parts by mass of the binder (solid content). By setting the amount of the flame retardant in such a range, it is possible to improve dispersibility and fire resistance.
[0045] In the present invention, it is preferable to use the flame retardant and the sodium tetraborate hydrate in combination, which can further improve fire retardancy, and in particular, by using a liquid flame retardant in combination, it is possible to control the dispersion stability of the sodium tetraborate hydrate and the viscosity of the composition, thereby obtaining a heat absorbing board with better fire retardancy.
[0046] Examples of the curing agent include organic peroxides such as hydroperoxides, dialkyl peroxides, diacyl peroxides, dialkyl ketone peroxides, ketone peroxides, peroxy esters, peroxy ketals, and peroxy dicarbonates; and azo compounds such as azobisisobutyronitrile, azobiscarbonamide, and 2-phenylazo-2,4-dimethyl-4-methoxyvaleronitrile. One or more of these may be used.
[0047] Examples of the dispersant include phosphate esters, polyphosphate esters, phosphate polyesters, polyether phosphate esters, and fatty acid esters, and one or more of these can be used. In the present invention, it is particularly preferable to use phosphate polyesters, which contribute to preventing the settling and separation of sodium tetraborate hydrate and maintain the fluidity of the endothermic composition for a long period of time, allowing the endothermic board to be easily manufactured. In particular, in the present invention, it is preferable to use phosphate polyesters having a solid content acid value of 30 mgKOH / g or more and 200 mgKOH / g or less, and further 40 mgKOH / g or more and 150 mgKOH / g or less. The solid content acid value is a value represented by mg of potassium hydroxide equivalent to the moles of acid groups contained in 1 g of solid content.
[0048] The amount of the dispersant mixed is preferably 0.1 to 5 parts by mass (more preferably 0.5 to 3 parts by mass) relative to 100 parts by mass of the binder (solid content). By using the dispersant in this range, the settling and separation of sodium tetraborate hydrate can be suppressed, and the fluidity of the endothermic composition can be maintained for a long period of time. Furthermore, during board production, warping and distortion can be suppressed, and an endothermic board with excellent formability can be obtained.
[0049] The endothermic composition may contain other metal hydrates in addition to the sodium tetraborate hydrate. Examples of such metal hydrates include sulfates such as ammonium aluminum sulfate dodecahydrate, sodium aluminum sulfate dodecahydrate, aluminum sulfate dodecahydrate, aluminum sulfate dodecahydrate, aluminum sulfate dodecahydrate, aluminum sulfate dodecahydrate, aluminum sulfate dodecahydrate, aluminum sulfate dodecahydrate, aluminum sulfate dodecahydrate, aluminum sulfate dodecahydrate, aluminum sulfate dodecahydrate, aluminum sulfate dodecahydrate, aluminum sulfate dodecahydrate, magnesium sulfate dodecahydrate, sodium sulfate dodecahydrate, nickel sulfate dodecahydrate, zinc sulfate dodecahydrate, beryllium sulfate dodecahydrate, and zirconium sulfate dodecahydrate; sulfites such as zinc sulfite dihydrate and sodium sulfite dodecahydrate; aluminum phosphate dihydrate, cobalt phosphate octahydrate, magnesium phosphate octahydrate, and the like; phosphates such as sium octahydrate, magnesium ammonium phosphate hexahydrate, magnesium hydrogen phosphate trihydrate, magnesium hydrogen phosphate heptahydrate, zinc phosphate tetrahydrate, and zinc dihydrogen phosphate dihydrate; nitrates such as aluminum nitrate nonahydrate, zinc nitrate hexahydrate, calcium nitrate tetrahydrate, cobalt nitrate hexahydrate, bismuth nitrate pentahydrate, zirconium nitrate pentahydrate, cerium nitrate hexahydrate, iron nitrate hexahydrate, iron nitrate nonahydrate, nickel nitrate hexahydrate, and magnesium nitrate hexahydrate; acetates such as zinc acetate dihydrate and cobalt acetate tetrahydrate; chloride salts such as cobalt chloride hexahydrate and iron chloride tetrahydrate; and borates such as disodium octaborate tetrahydrate and zinc borate 3.5-hydrate.
[0050] The heat absorbing board can be manufactured by known methods such as injection molding, extrusion molding, pultrusion molding, compression molding, rotational molding, thermoforming, hot melting, blow molding, transfer molding, bulk molding, hand lay-up method, spray-up method, matched die method, filament wind method, sheet molding method, cold press method, SMC method, BMC method, and preform matched die method.
[0051] Specifically, for example, the unsaturated polyester, the unsaturated monomer, and the sodium tetraborate hydrate are mixed, and other additives are added and mixed as necessary, and cured to obtain an endothermic board. In particular, a first liquid (first component) containing the unsaturated polyester, the unsaturated monomer, and the sodium tetraborate hydrate, and other additives as necessary, and a second liquid (second component) containing a curing agent are prepared, and the first liquid and the second liquid are mixed and reacted to obtain an endothermic board. In such a case, it is particularly preferable to mix and react at a temperature of 10°C or higher and 70°C or lower (more preferably 15°C or higher and 50°C or lower).
[0052] The density of the heat absorbing board is 0.8 g / cm 3 More than 2.0g / cm 3 Less than (more preferably 1.0 g / cm 3 More than 1.9g / cm 3 More preferably, 1.2 g / cm 3 More than 1.7g / cm 3 It is preferable that
[0053] The thickness of the heat absorbing board is preferably 3 mm or more and 60 mm or less (more preferably 4 mm or more and 50 mm or less, even more preferably 5 mm or more and 30 mm or less, and most preferably 6 mm or more and 25 mm or less).
[0054] The heat-absorbing board of the present invention can be applied to, for example, building components such as roofs, ceilings, walls, floors, doors, beams, and pillars, as well as vehicle components and electronic components, and can be used by laminating it with boards or films made of materials such as metal, plastic, mortar, cement, gypsum, wood, paper, and fiber. In the present invention, it is particularly preferable to apply it to wood materials, plastic materials, paper materials, fiber materials, and the like. Since the heat-absorbing board of the present invention is suppressed in warping and distortion, it can be easily applied to the above-mentioned building materials, vehicle materials, and electronic materials, and the work efficiency during construction can be improved.
[0055] Examples of the wood materials include Japanese cypress, cedar, Japanese hiba, Japanese pine (Japanese pine, larch, Yezo spruce, Abies sachalinensis, and spruce), Douglas fir, Norway spruce, Norway scotch pine, etc., and they can be used as lumber, plywood, laminated lumber, LVL (Laminated Veneer Lumber), CLT (Cross Laminated Timber), particle board, fiberboard, square pillars, etc. The use of such wood materials also contributes to the promotion of carbon neutrality, etc. Furthermore, the square pillars are not limited to being rectangular, and may be polygonal.
[0056] Among the wood materials, the CLT is called cross-laminated timber, which is a wood material in which sawn boards (lamina) are arranged and then laminated so that the fiber direction is perpendicular. Specifically, CLT is defined in the Japanese Agricultural Standard JAS3079:2019 "Cross-laminated timber" as "wood in which sawn boards or small square timbers (including those adjusted by joining and gluing them in the length direction with their fiber directions approximately parallel to each other) are arranged or glued in the width direction with their fiber directions approximately parallel to each other, and are mainly laminated and glued with their fiber directions approximately perpendicular to each other to have a structure of three or more layers." By using CLT as a wood substrate, it becomes possible to apply the laminate of the present invention to structural members (structural bodies), columns, etc.
[0057] The thickness of the wood material can be appropriately set depending on the application, etc.
[0058] The plastic material may be a material containing a thermoplastic resin and / or a thermosetting resin as a main component.
[0059] Examples of the thermoplastic resin include polyamide, polyacetal, polysulfone, polyester, polybutylene terephthalate, polycarbonate, polyethylene terephthalate, polyethylene, polypropylene, polyphenylene sulfide, polyether ether ketone, polyether imide, polyether ketone ketone, polyvinyl chloride, acrylic resin, ABS resin, fluororesin, and silicone resin.
[0060] As the thermosetting resin, those that form a three-dimensional crosslinked structure by a crosslinking reaction can be used, and examples thereof include unsaturated polyester resins, vinyl ester resins, epoxy resins, benzoxazine resins, phenolic resins, urethane resins, urea resins, melamine resins, polyimide resins, etc. These can be used alone or in combination of two or more.
[0061] In the present invention, a fiber-reinforced plastic material can be used as the plastic material. The fiber-reinforced plastic material is a composite of the above-mentioned resin and fiber, and is a material having properties such as high specific rigidity and high specific strength. By using a fiber-reinforced plastic material as the plastic material, it becomes possible to apply the laminate of the present invention to structural members (structural bodies) and the like.
[0062] Examples of the fibers used in the fiber-reinforced plastic material include glass fibers, aramid fibers, Kevlar (registered trademark) fibers, carbon fibers, graphite fibers, boron fibers, Tyranno fibers, silicon carbide fibers, silicon nitride fibers, alumina fibers, and mineral fibers, and among these, glass fibers and carbon fibers are preferred from the viewpoint of improving mechanical strength, and glass fibers are also preferred from the viewpoint of cost. These can be used alone or in combination of two or more kinds.
[0063] The thickness of the plastic material can be appropriately set depending on the application, etc.
[0064] In the present invention, two or more heat absorbing boards may be stacked, and various materials may be laminated as necessary, provided that the effects of the present invention are not significantly impaired. Examples of such materials include an adhesive layer, a decorative layer, a reinforcing material layer, and other layers (e.g., a heat reflective layer, a heat shielding layer, a waterproof layer, a water repellent layer, a water shielding layer, a heat insulating layer, etc.).
[0065] Among these, the adhesive layer is formed by the heat absorbing board, the adhesive used when bonding each layer, etc. As the adhesive used for the adhesive layer, for example, known adhesives such as water-dispersed, water-soluble, and solvent-based adhesives using acrylic resin, silicon resin, epoxy resin, vinyl resin, phenolic resin, polyester resin, urethane resin, paraffin, etc. as the main raw material can be used.
[0066] As the decorative layer, for example, woodblocks, particle boards, fiberboards, various coating materials, sheet materials, film materials, etc. can be used. These can have various appearances such as transparent or opaque, colorless or colored, non-glossy or glossy, monochromatic or multicolored, flat or uneven, etc. In the present invention, the provision of the decorative layer is useful because it can improve aesthetics, water resistance, weather resistance, etc.
[0067] The reinforcing material layer may be, for example, a nonwoven fabric, a woven fabric, or a woven material, and one or more of these may be used in combination. Nonwoven fabrics are fabrics (sheets) made of independent fibers (formed without weaving), such as fabrics with crossed fiber arrangements, random fiber arrangements, etc. Furthermore, methods for bonding fibers include chemical adhesion using a resin component (chemical bonding), fusion by heating (thermal bonding), mechanical intertwining (needle punching), stitching (stitch bonding), etc. Examples of woven fabrics include those in which fibers aligned in one direction and fibers aligned in a different direction are woven vertically, horizontally, or diagonally and laminated together. The woven fabric may have a mesh structure, and examples of such woven fabrics include multi-axial woven fabrics such as biaxial woven fabrics, triaxial woven fabrics, and quadraxial woven fabrics, depending on the number of axes of the fiber groups. Woven fabrics are formed from fibers in the same way as woven cloth, and are woven by interlacing warp and weft fibers above and below. Examples of woven fabric structures include plain weave, twill weave, satin weave, double warp weave, double weft weave, double warp and weft weave, pile weave, leno weave, and figured weave.
[0068] Examples of fibers used in the reinforcing layer include inorganic fibers such as rock wool, glass fibers, silica fibers, silica-alumina fibers, carbon fibers, silicon carbide fibers, and the like; fine metal wires such as iron and copper; and organic fibers such as pulp fibers, polyester fibers, polypropylene fibers, aramid fibers, vinylon fibers, polyethylene fibers, polyarylate fibers, PBO fibers, nylon fibers, acrylic fibers, vinyl chloride fibers, and cellulose fibers. One or more of these may be used.
[0069] In the present invention, it is particularly preferable to use a nonwoven fabric in which fibers are randomly arranged as the reinforcing material layer, and it is particularly preferable to use an inorganic fiber nonwoven fabric in which inorganic fibers are randomly arranged and bonded between the inorganic fibers with a resin component. Furthermore, it is preferable to use glass fibers as the inorganic fibers. Such a reinforcing layer can reinforce the strength of the heat absorbing board, as well as the fire resistance and formability.
[0070] The thickness of the reinforcing material layer is preferably about 0.1 to 3 mm, and more preferably about 0.15 to 2 mm.
[0071] When laminating the reinforcing material layer and the heat absorbing board, they can be attached to each other using the adhesive layer, or the reinforcing material layer can be embedded in the heat absorbing board, or the reinforcing material layer can be laminated on one or both sides of the heat absorbing board. In the method of embedding the reinforcing layer in the endothermic board, when the endothermic composition is cured to obtain the endothermic board, the reinforcing layer can be embedded in the endothermic composition before the endothermic composition is cured, and then cured to obtain the endothermic board. Specifically, the method includes pouring an endothermic composition containing a binder and sodium tetraborate hydrate onto a reinforcing material layer and curing the composition; A method of spraying sodium tetraborate hydrate on a reinforcing material layer, pouring a composition containing a binder, and hardening the composition; A method of pouring a composition containing a binder onto a reinforcing material layer, further spraying sodium tetraborate hydrate thereon, and then hardening the composition; Alternatively, after pouring the endothermic composition, a reinforcing layer may be laminated on the endothermic composition before the endothermic composition is cured. The endothermic composition may then be poured and cured. The degree of embedding is not particularly limited, but may be a fully embedded state in which the reinforcing material layer is entirely embedded, or a semi-embedded state in which only a portion of the reinforcing material layer is exposed to the surface. In the present invention, the strength, fire resistance, and formability of the heat absorbing board can be further improved by using a reinforcing layer into which the binder of the heat absorbing composition permeates but which sodium tetraborate hydrate does not easily permeate. 2 , and even 20 to 300 g / m 2 It is preferable that: EXAMPLES
[0072] The features of the present invention will be more clearly described below with reference to examples and comparative examples, but the present invention should not be construed as being limited to these examples.
[0073] [Example 1] An endothermic composition was produced by mixing and stirring the raw materials and compositions shown in Table 1, a binder, and sodium tetraborate under standard conditions (temperature 23°C, relative humidity 50%). After producing the endothermic compositions, they were left to stand under standard conditions for a specified time (2 hours, 24 hours), and then the curing agent 1 was mixed and stirred into each endothermic composition, poured into a formwork (100 mm x 100 mm, thickness 12 mm), reacted for 3 hours, and demolded to obtain endothermic boards. At this time, the following forming property test 1, forming property test 2, and endothermic property test were carried out. The results are shown in Table 1. Note that the endothermic property test was carried out only after leaving the sample to stand for the specified time of 2 hours.
[0074] [Formation test 1] The endothermic composition was left to stand under standard conditions for a specified time (2 hours, 24 hours), and then the state of the endothermic composition was evaluated. The evaluation criteria are as follows. Note that, as a practical level, the evaluation criteria of AA and A are preferable. AA: Endothermic composition left standing for 24 hours Sufficient fluidity was observed, and no separation of sodium tetraborate was observed. A: In an endothermic composition left standing for 2 hours, Sufficient fluidity was observed, and no separation of sodium tetraborate was observed. X: In an endothermic composition having a standing time of 2 hours, Fluidity was lost, or separation of sodium tetraborate was observed.
[0075] [Formation test 2] The obtained heat absorbing board was placed on a horizontal test table and left to stand for 24 hours under standard conditions, and the state (warping) of the heat absorbing board was observed and evaluated. The evaluation criteria are as follows. For practical use, the evaluation criteria of AA and A are preferable. AA: Endothermic board obtained from endothermic composition left for 24 hours. The maximum distance (mm) between the test table and the edge or center of the heat absorption board is less than 0.5 mm. A: In an endothermic board obtained from an endothermic composition that has been left standing for 2 hours, The maximum distance (mm) between the test table and the edge or center of the heat absorption board is less than 0.5 mm. X: In an endothermic board obtained from an endothermic composition that has been left standing for 2 hours, The maximum distance (mm) between the test table and the end or center of the heat absorption board is 0.5 mm or more.
[0076] [Endothermic test] A reinforced gypsum board (thickness 12.5 mm) was bonded to the obtained heat absorbing board with an acrylic adhesive to obtain a test specimen. The heat absorbing test was carried out using a cone calorimeter specified in ISO 5660. The heating intensity was 50 kW / m 2The heating time was 60 minutes. In the heat absorption test, the temperature of the back side of the test specimen was measured during heating, and the maximum temperature reached was used for evaluation. The back side of the test specimen here refers to the heat absorption board side, the side that was not heated. The evaluation criteria are as follows: For practical use, the evaluation criteria of AA and A are preferable. (Evaluation Criteria) AA: Maximum temperature is 200℃ or less A: The maximum temperature is over 200℃ and below 250℃ X: Maximum temperature exceeds 250℃
[0077] [Examples 2 to 14, Comparative Example 1] Using the raw materials and compositions shown in Table 1, endothermic boards and test specimens were obtained in the same manner as in Example 1, and formability test 1, formability test 2, and endothermic test were carried out in the same manner as in Example 1. The results are shown in Table 1.
[0078] [Table 1]
Claims
1. a binder and sodium tetraborate hydrate; The binder comprises an unsaturated polyester and an unsaturated monomer. An endothermic composition comprising:
2. 2. The endothermic composition according to claim 1, wherein the sodium tetraborate hydrate is contained in an amount of 30 parts by mass or more and 300 parts by mass or less per 100 parts by mass of the binder.
3. 2. The endothermic composition of claim 1, wherein the sodium tetraborate hydrate comprises sodium tetraborate decahydrate.
4. 2. The endothermic composition according to claim 1, further comprising a layered clay mineral.
5. 5. The endothermic composition according to claim 4, wherein a mixing ratio (weight ratio) of said binder to said layered clay mineral is 100:0.1 or more and 100:8 or less.
6. The mixing ratio (mass ratio) of the sodium tetraborate hydrate to the layered clay mineral is 100:0.1 or more and 100:10 or less.
5. The endothermic composition according to claim 4.
7. 5. The endothermic composition according to claim 4, wherein the layered clay mineral comprises bentonite.
8. A heat absorbing board formed from the heat absorbing composition according to any one of claims 1 to 7.
Citation Information
Patent Citations
Non-combustible improved gypsum board
JP1997302804A
Incombustible fiber reinforced resin molded body and manufacturing method therefor
JP2019006852A